Life cycle and population parameters of Aceria malherbae in field bindweed: a laboratory approach - Martínez-Argüello, Fátima; Cerna-Chávez, Ernesto; Vega-Verdugo, Alicia; Landeros-Flores, Jerónimo (Revista Mexicana de Ciencias Agrícolas, 2025)
The weed Convolvulus arvensis L. (Solanales: Convolvulaceae) was introduced and is native to the Mediterranean region of Europe; it is currently widely distributed throughout the world. Eriophyid mites, in the case of weeds, are considered to have great potential as biological control agents; these attributes are due to their monophagous or oligophagous habit, which makes them highly specific. Within the mites associated with this plant, the species Aceria malherbae Nuzzaci (Acari: Eriophyidae) has been reported, a gall mite that inhabits the midribs of the leaves and causes their deformation. The high degree of specificity of the mite in feeding on C. arvensis makes it an optimal candidate for controlling this weed. The objective of this research was to determine the life cycle and population parameters (Ro, rm, TG, t2 and λ) of Aceria malherbae on plants of field bindweed, Convolvulus arvensis (Solanales: Convolvulaceae). The experiment was conducted from June 2023 to June 2024; the collection took place in agricultural fields where the weed had previously been infested by members of the Local Board of Plant Health of the Yaqui Valley in Ciudad Obregón, Sonora. The samples were transferred to the Department of Agricultural Parasitology of the Antonio Narro Autonomous Agrarian University, and a mother colony of A. malherbae was established under laboratory conditions. Aceria malherbae completed its cycle in 12.29 days. The fecundity rate was 23.83 eggs laid per female on average in 13 days (e/f/d); likewise, the population parameters Ro, rm, and λ were 18.87, 0.54, and 1.72, respectively. The development time of the second generation (TG) was 5.4, and the population doubling time (t2) was 1.27. The population parameters and life cycle determined in this study confirm the rapid growth of the populations of the mite A. malherbae; these metrics explain why it became an important biological control agent. The values obtained allowed us to understand the impact of its activity in the field when it encounters favorable conditions for its multiplication and development. This positions it as an important alternative for controlling weed C. arvensis and highlights the relevance of continuing research on its biology in order to promote its use.
Keywords: Aceria malherbae; Convolvulus arvensis; population; weeds